2022
DOI: 10.1021/jacs.2c06578
|View full text |Cite
|
Sign up to set email alerts
|

Migrative Carbofluorination of Saturated Amides Enabled by Pd-Based Dyotropic Rearrangement

Abstract: Directly editing an all-carbon quaternary carbon itself of nonstrained acyclic molecules remains underexploited despite the recent advances in the fields of both C–H and C–C bond activation. Herein, we report a palladium-catalyzed migrative carbofluorination of saturated amides enabled by the activation of both the C­(sp3)–H and the Cquaternary–Cσ bonds. In this transformation, the α-quaternary carbon of Weinreb amides is converted to α-tertiary fluoride with concurrent migration of an aryl or an amido group f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

7
1

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 51 publications
0
11
0
Order By: Relevance
“…Functionalized methyleneadamantanones 17a to 17d (R = COOH and OH, X = H, H and O) were likewise transformed to homoadamantanones 18a to 18d. Benzocyclooctan-7-one (20), which is difficult to access by conventional cyclization methods, was obtained in good yield through ring expansion of 7-methylenebenzocycloheptane (19). Finally, ring expansion of macrocycles proceeded smoothly, generating the 13-and 16-membered cycloalkanones 22 and 24 from the 12-and 15-membered methylenecycloalkanes 21 and 23, respectively, in good yields.…”
Section: Reaction Scopementioning
confidence: 99%
“…Functionalized methyleneadamantanones 17a to 17d (R = COOH and OH, X = H, H and O) were likewise transformed to homoadamantanones 18a to 18d. Benzocyclooctan-7-one (20), which is difficult to access by conventional cyclization methods, was obtained in good yield through ring expansion of 7-methylenebenzocycloheptane (19). Finally, ring expansion of macrocycles proceeded smoothly, generating the 13-and 16-membered cycloalkanones 22 and 24 from the 12-and 15-membered methylenecycloalkanes 21 and 23, respectively, in good yields.…”
Section: Reaction Scopementioning
confidence: 99%
“…Finally, a dyotropic rearrangement of int V gives the desired γ-lactone 3a . It should be noted that an alternative pathway cannot be excluded currently; the Pd IV int IV may undergo direct dyotropic rearrangement to generate int V′ , followed by in situ reductive elimination to produce product 3a . Further investigations may provide additional insights into the mechanistic details of the reaction.…”
mentioning
confidence: 99%
“…Dyotropic rearrangement is a process in which two σ-bonds migrate simultaneously. We have recently discovered that Pd­(IV) species, formed via oxidation of the in situ generated C­(sp 3 )-Pd­(II) complex, can undergo facial 1,2-aryl/Pd­(IV) dyotropic rearrangement to afford compounds that are otherwise difficultly accessible. While a 1,2-rearrangement affords, in its basic form, the constitutional isomer, it can also lead to the ring-expansion/contraction products and topologically different molecules when the migrating groups are embedded in a complex polycyclic system . Therefore, integration of a Pd­(IV)-based dyotropic rearrangement into a given transformation is likely to change the product structure significantly.…”
mentioning
confidence: 99%
“…Therefore, integration of a Pd­(IV)-based dyotropic rearrangement into a given transformation is likely to change the product structure significantly. In our previous studies, we observed that aryl groups have a higher migratory aptitude than that of sp 3 -carbon and that the migration of more substituted C­(sp 3 ) prevails over the less substituted one (Scheme b) in this 1,2-postional exchange process . To fully exploit the synthetic potential of this Pd­(IV)-based dyotropic rearrangement, we became interested in examining the relative migratory aptitude of oxygen vs carbon atoms (Scheme c) and Pd­(II)-catalyzed cyclization of γ-hydroxyalkenes 1 was deemed to be an ideal reaction to investigate.…”
mentioning
confidence: 99%